Exchange Rate and Interest Rate in the Monetary Policy Reaction Function - Borivoje D. Krušković (Journal of Central Banking Theory and Practice, 2017)
In recent years there has been a particular interest in the relation between exchange rates and interest rates both in developed countries and emerging countries. This is understandable given the important role that these variables have in determining the movement of nominal and real economic variables, including the movement of domestic inflation, real output, exports and imports, foreign exchange reserves, etc. To realized the importance of the given instruments selected macroeconomic indicators, data analysis (monthly data) relating to Serbia was made on the basis of the Transfer Function Model, a data analysis (annual data) relating to emerging countries was done on the basis of the Stepvise Multiple Regression model. In the transfer function model we used the Maximum Likelihood method for assessing unknown coefficients. In the gradual multiple regression model we used the Least Square method for the evaluation of unknown coefficients. All indicator values were used in the original unmodified form, i.e. there was no need for a variety of transformations. Empirical analysis showed that the exchange rate is a more significant transmission mechanism than the interest rate both in emerging markets and Serbia.
Keywords: E31; E41; E52; 330; exchange rate; interest rate; monetary policy